Análisis fitoquímico y cuantificación de fenoles totales en frutos de Syzygium paniculatum Gaertn.: Phytochemical analysis and quantification of total phenols in fruits of Syzygium paniculatum Gaertn. - Salgado Cepeda, David (2025)
The present study aimed to phytochemically characterize and quantify the total polyphenol content in fruits of Syzygium paniculatum Gaertn., a little-studied species but with bioactive potential. Qualitative and semiquantitative phytochemical screening methods were used, as well as the Folin-Ciocalteu method to determine total phenols. The fruits were collected in Quito, Ecuador, and processed to obtain extracts with three hydroalcoholic mixtures: methanol-water (80%), ethanol-water (80%), and acetone-water (80%). Screening revealed abundant flavonoids and tannins, and moderate anthocyanidins and reducing sugars, while alkaloids, triterpenes, saponins, and other metabolites were not detected. Regarding the quantification of polyphenols, the results showed that the methanol-water extract (80%) presented the highest content (86.67 ± 1.94 mg EAG/100 g of dried fruit), followed by ethanol-water (80.29 ± 1.30 mg EAG/100 g) and acetone-water (66.94 ± 0.90 mg EAG/100 g). The differences between extracts were statistically significant (ANOVA, p < 0.05). These findings are consistent with previous studies in other species of the genus Syzygium, where polar solvents show greater extraction efficiency. In conclusion, S. paniculatum fruits are a relevant source of phenolic compounds with potential application in functional foods and nutraceuticals. The methanol-water combination (80%) was identified as the most efficient extraction system, although ethanol-water represents a promising option due to its lower toxicity. It is recommended to expand research to include studies of specific biological activity and optimization of extraction techniques.